Risen from the Dead: From Slumming to Gentrification - Mart HIOB; Nele NUTT; Sulev NURME; Fransesco DE LUCA (Transylvanian Review of Administrative Sciences, 2012)
Political tides are evident in most community development practices. Sometimes it hinders good planning while at other times it aides development, and sometimes the unintended consequences of politics preserve neighborhoods for a long time, allowing for a totally different development outcome. This article is a detailed case study of one such neighborhood. This neighborhood, known as Supilinn, in Tartu Estonia was a rundown area slated for total demolition during Soviet occupation. Due to the lack of finances and low priorities, the former communist regime abandoned the idea of demolition and left the neighborhood to deteriorate further. Two decades later, Supilinn is a bustling community where young and old, rich and poor, existing and new, all co-exist. A community left to die has resurrected itself through bottom up planning and citizen initiatives to become one of the preferred places to live, so much so that the neighborhood now faces the threat of gentrification with social displacement and complete renewal. The authors, all active members in this neighborhood, have lived and worked there for a while. They tell the story of many such transformations across the landscape through the lens of one case study.